Gun Pulled on Three Pan Judges - Unknown (Daily Express)
Three judges, who officiated at the national Panorama finals, were reported to have been threatened by a man with a gun following the announcement of the results at Queen's Park Savannah, Port of Spain. This incident is going to make it tough for Panorama organizers to get judges in the future.
Keywords: Steel bands (Music) -- Competitions -- Judging; Steel bands (Music) -- Competitions -- Trinidad and Tobago; Panorama (Musical festival); Steel bands (Music) -- Trinidad and Tobago